WH-QUESTIONS TECHNIQUE GUIDE FOR MASTERING AND IMPROVING THE STUDENTS’ SPEAKING SKILL - Listyowati, Rini; Hanna, Ina Daril; Yunitaka B., Dinar Vincy (Universitas Islam Lamongan, 2023)
This research was conducted using a classroom action research design through two cycles. The purpose of the study is to know how Guided WH-Questions technique are able to increase the speaking skill of the students at Junior High School. The research was conducted at SMP Al-Islamiyah Teja Barat Pamekasan. It is limited only at the first grade and the class consists of 19 students. The data was collected through observation sheet, field notes, the students’ test and questionnaire. In data analysis, the researcher utilized descriptive quantitative. The data from the outcome of observation and the students’ test are analyzed utilizing statistic analysis. The findings showed that the students’ involvement in learning process indicated the success of the teaching and learning if in the cycle 1 of meeting 1 was 77% and meeting 2 was 85,7%. Then. In second cycle of meeting 1 the students’ involvement improved to be 91, 4% and meeting 2 was 97%. The refinement was seen from the advance of the students’ average speaking points. In preliminary study, the students’ speaking average score was 54, 8. It improved to be 71 in the cycle 1 and 82 in the cycle 2. While the students’ outcome of the questionnaire showed the students were fascinated and enjoyed in studying speaking through Guided WH-Question.